Georgia Architectural and Historic Properties Survey of Rural [023] East section of the county, Ousley, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [023] East section of the county, Ousley, Ga. December 1980. A one story L-shaped with gabled tin roof and clapboard siding. Shed porch with turned spindle posts. Sash windows with 2/2 lights. Brick piers. Fair condition. Date of Construction: Unknown. A typical L-shaped house common to the rural Brooks County.
Georgia Architectural and Historic Properties Survey of Rural [023] East section of the county, Ousley, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.51 MB (1,587,540 bytes).
Keywords: Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Ousley (Ga.)